An updated reappraisal of synapsins: structure, function and role in neurological and psychiatric disorders. (November 2021) - Longhena, Francesca; Faustini, Gaia; Brembati, Viviana; Pizzi, Marina; Benfenati, Fabio; Bellucci, Arianna
Highlights: Three evolutionary conserved Synapsins genes have been identified. Synapsins are involved in neuronal development and neurotransmitter release. Synapsins exhibit distinctive localization, expression and post-translational modifications. Synapsins alterations underlie the onset of multiple brain disorders. Spotlight on the role of Synapsins in psychiatric and neurological disorders. Abstract: Synapsins (Syns) are phosphoproteins strongly involved in neuronal development and neurotransmitter release. Three distinct genes SYN1, SYN2 and SYN3, with elevated evolutionary conservation, have been described to encode for Synapsin I, Synapsin II and Synapsin III, respectively. Syns display a series of common features, but also exhibit distinctive localization, expression pattern, post-translational modifications (PTM). These characteristics enable their interaction with other synaptic proteins, membranes and cytoskeletal components, which is essential for the proper execution of their multiple functions in neuronal cells. These include the control of synapse formation and growth, neuron maturation and renewal, as well as synaptic vesicle mobilization, docking, fusion, recycling. Perturbations in the balanced expression of Syns, alterations of their PTM, mutations and polymorphisms of their encoding genes induce severe dysregulations in brain networks functions leading to the onset of psychiatric or neurological disorders. This review presents what we have learned since the discovery of Syn I in 1977, providing the state of the art on Syns structure, function, physiology and involvement in central nervous system disorders.